Induction and Deduction in Theorizing of International Relations - Gałganek, Andrzej (Wydawnictwo Naukowe WNPiD UAM, 2019)
The article presents the ways of understanding the place of induction and deductive reasoning in the process of building the theory and knowledge of international relations and the resulting disputes present in the International Relations. The author argues that in the study of international relations, as in the natural sciences, it is necessary to combine empirical observation with creative building of theory. The author performs a critical analysis of the positions of selected theoreticians of international relations on issues related to the problems of induction and deduction and theorizing of international relations.

W artykule ukazano obecne w nauce o stosunkach międzynarodowych sposoby rozumienia miejsca indukcyjnego i dedukcyjnego wnioskowania w procesie budowania teorii i wiedzy o stosunkach międzynarodowych oraz wynikające z nich spory. Autor argumentuje, że w badaniu stosunków międzynarodowych, podobnie jak w naukach przyrodniczych, niezbędne jest łączenie empirycznej obserwacji z kreatywnym budowaniem teorii. Autor dokonuje krytycznej analizy stanowisk wybranych teoretyków stosunków międzynarodowych w kwestiach związanych z problemami indukcji i dedukcji oraz teoretyzowania stosunków międzynarodowych.
Indukcja i dedukcja w teoretyzowaniu stosunków międzynarodowych
Keywords: induction; deduction; theory; International Relations; indukcja; dedukcja; teoria; nauka o stosunkach międzynarodowych